PENGENALAN FAUNA SERANGGA MELALUI JELAJAH ALAM SEKITAR (JAS) DAN BERMAIN UNTUK MENGEMBANGKAN KECERDASAN NATURALIS BAGI ANAK-ANAK DI SEKOLAH ALAM YOMBE YAWA DATUM KAMPUNG RHEPANG MUAIF, NIMBOKRANG, KABUPATEN JAYAPURA - Warikar, Evie L.; Ramandey, Euniche R.P.F.; Waisimon, Alexandra (JURNAL PENGABDIAN PAPUA, 2024)
The main objective of this activity is to introduce the local insect fauna and its ecological function to the children of Yombe Yawa Nature School Datum Rhepang Muaif Village using fun methods, namely Exploring the Natural Environment (JAS), telling stories and playing insect fauna educational puzzles to increase their intelligence. This activity was carried out on September 7 2024 at the Yombe Yawa Datum Nature School, Rhepang Muaif Village, Nimbokrang, Jayapura-Papua involving 25 participants from representatives of early childhood/pre-school, elementary school grades 1–6, junior high school grades 1–3 and SMA class 1. The activity began with providing material regarding an introduction to the biodiversity of insect fauna in general in Papua. After that, we continued by inviting the children to walk to explore the natural surroundings, starting from the school yard, garden, river to the footpath in the tourist forest area, while observing the various insect fauna encountered along the exploration. To evaluate the results of the service, activities were carried out such as pre-test, post-test, and playing insect fauna puzzles to test children's memory for insect fauna that had been introduced previously. The results show that there is an increase in children's knowledge about insect fauna. Children are able to recognize several local insect faunas that are unique to their area, as well as understand the ecological role of insect fauna in the environment and develop a sense of love for the insect fauna around them. From this level of understanding, the character of caring for insect fauna begins to form and an attitude of wanting to protect the environment emerges.  Keywords: Insect; JAS method; Naturalist Intelligence; Rhepang Muaif